The Environment at Lake El’gygytgyn Area (Northeastern Russian Arctic) Prior to and After the Meteorite Impact at 3.58 Ma - Andreev, Andrei; Dietze, Elisabeth; Glushkova, Olga; Smirnov, Vladimir; Wennrich, Volker; Melles, Martin (Frontiers in Earth Science, 2021)
Upper Pliocene sediments from a number of fluvial outcrops in central Chukotka, northeastern Russian Arctic, along the Enmyvaam, Mechekrynnetveem, and Chanuvenvaam Rivers, have been newly studied for pollen, non-pollen-palynomorphs and, for the first time for Pliocene sediments in Eurasia, charcoals. The sediments have survived the El’gygytgyn meteorite impact event at ~3.58 Ma. The stratigraphy of the studied outcrops suggests that the lowermost sediments were accumulated shortly before the impact event, between ~3.60 and 3.58 Ma. At that time, coniferous forests with spruces, pines, firs, birches, larches, and alders dominated in the area. Some relatively thermophilic broad-leaved taxa (Corylus, Carpinus, Ulmus, Myrica) might also have grown in local forests. Summer temperatures were at least 10°C warmer than today. Charcoal concentrations and composition suggest the presence of high intensity fires. Periods of rather wet climate and soil conditions are marked by common shrubby and boggy habitats with ericaceous plants and Sphagnum, and are associated with less, and probably low-intensity surface fires with less charcoal. The impact event caused widespread fires reflected by up to 4 times higher charcoal concentrations in the sediments. The sediments found above the so-called ´chaotic horizon´ (sediments accumulated synchronously or very shortly after the impact event) contain late Pliocene pollen assemblages comparable to those in Lake El’gygytgyn, reflecting that pine-spruce forests with some firs, birches, larches, and alder dominated in the study area. Some thermophilic taxa might also still have grown in the area. However, the age control for the sediments above the so-called chaotic horizon is poor. The uppermost sediments from the studied sections can be attributed with certainty to the Late Pleistocene and Holocene according to their stratigraphic positions and pollen assemblages. The combined pollen and charcoal analysis allowed correlating hardly datable fluvial sediments and points to varying fire regimes in warmer-than-present climates, when forest extended farer? north compared to today.